From awareness to action: Unveiling knowledge, attitudes and testing strategies to enhance human papillomavirus vaccination uptake in Jordan - Ahmad Al-leimon; Obada Al-leimon; Bayan Abdulhaq; Fadi Al-salieby; Abdul-Raheem Jaber; Mohammed Saadeh; Abdel Rahman Jaber; Omer Aziziye; Latefa Ali Dardas (Elsevier, 2024)
Purpose: Vaccination against HPV plays a crucial role in preventing cervical cancer and related health issues. This study aimed to (1) assess knowledge, awareness, intentions, and attitudes regarding HPV and vaccination among Jordanian parents, and (2) evaluate the efficacy of two intervention strategies in promoting knowledge, awareness, and attitudes towards HPV vaccinations. Methods: In study one, a web-based survey was used to collect data from Jordanian parents. In study two, participants were allocated into three groups: video-based intervention, lecture-based intervention, and a control group. Pre-post tests were conducted to evaluate the efficacy of the intervention strategies in promoting knowledge, awareness, and attitudes toward HPV vaccination among Jordanian parents. Results: A total of 572 participants took part in the survey. Knowledge levels about HPV and its vaccine were generally low. Intentions regarding HPV vaccination were uncertain for the majority of participants, with 92 % reported as not receiving any guidance from medical professionals about administering the HPV vaccine to themselves or their children. Only 22 % agreed that their children might get infected with HPV at any time in their lives. The pilot randomized clinical trial revealed an improvement in knowledge, awareness, and attitudes towards HPV vaccination in both intervention groups compared to the control group with large effect sizes (eta squared between 0.29 and 0.68). Conclusions: Findings highlight the need for increased knowledge and awareness regarding HPV and vaccination. It also supported the potential effectiveness of basic educational efforts in significantly improving knowledge, awareness, and attitudes towards the HPV vaccine.